Torsion units for some projected special linear groups - Joe Gildea (International Journal of Group Theory, 2017)
In this paper, we investigate the Zassenhaus conjecture for $PSL(4,3)$ and $PSL(5,2)$. Consequently, we prove that the Prime graph question is true for both groups.